Structure and function of USP5: Insight into physiological and pathophysiological roles. (July 2020) - Ning, Fengling; Xin, Hong; Liu, Junqiu; Lv, Chao; Xu, Xin; Wang, Mengling; Wang, Yinhang; Zhang, Weidong; Zhang, Xuemei
Graphical abstract: Abstract: Deubiquitinase (DUB)-mediated cleavage of ubiquitin chains from substrate proteins plays a crucial role in various cellular processes, such as DNA repair and protein stabilization and localization. DUBs can be classified into five families based on their sequence and structural homology, and the majority belong to the ubiquitin-specific proteinase (USP) family. As one of the USPs, ubiquitin-specific proteinase 5 (USP5) is unique in that it can specifically recognize unanchored (not conjugated to target proteins) polyubiquitin and is essential for maintaining homeostasis of the monoubiquitin pool. USP5 has also been implicated in a wide variety of cellular events. In the present review, we focus on USP5 and provide a comprehensive overview of the current knowledge regarding its structure, physiological roles in multiple cellular events, and pathophysiological roles in relevant diseases, especially cancer. Signaling pathways and emerging pharmacological profiles of USP5 are also introduced, which fully embody the therapeutic potential of USP5 for human diseases ranging from cancer to neurological diseases.